Closing The Digital Gender Gap In Indonesia Through The Roles And Initiatives Of Civil Society Organizations - Bahagijo, Sugeng; Prasetyo, Yanu Endar; Kawuryan, Denisa; Tua, Bona; Eridani, Aditiana Dewi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The digital gender gap is still a big, unseen problem in Indonesia. The government alone will not be able to close this gap, and it needs support from the private sector and the role of civil society. This study aims to explore and determine Civil Society Organizations’ (CSOs) role in closing the digital gender gap in Indonesia. Using a qualitative approach, this research collected data and information through interviews and focus group discussions with CSO representatives who have long been advocating for various vulnerable groups of women in Indonesia. Multiple literatures and reports related to the digital gender divide were also reviewed. An important finding in this study is the description and exploration of the various roles of CSOs in digital assistance to women and vulnerable groups through a wide range of programs such as (1) advocating for women’s rights, (2) promoting digital literacy, (3) fulfilling the Rights to Sexual and Reproductive Health, (4) protecting women victims of violence, (5) public policy oversight, (6) encouraging women’s public/political participation, (7) securing recognition of marginalized groups, (8) women’s economic empowerment, and (9) environmental sustainability campaigns. The results of this research indicate that CSOs have directly or indirectly contributed to increasing the capacity of individual women and groups they engage with. The various digital mentoring roles performed by CSOs have helped women and other vulnerable groups to become more confident, thereby increasing their participation in the public sphere, mainly through the use of ICT/the internet.